The relationship between motivation and English language test performance among secondary vocational schools’ students in China - Qiu Chuane; Siti Shuhaida Shukor; Tian Yuehong; Zhong Xiaofen (Studies in English Language and Education, 2023)
In China, secondary school students studying at the vocational stream often struggle to keep up with English language learning. This study investigates the relationship between two types of motivation – extrinsic and intrinsic – towards the English language test performance of students from a secondary vocational school in Chongqing, China. A mixed-method research design was employed via a survey and a semi-structured interview. A total of 212 second-grade students at randomly selected secondary vocational schools completed the questionnaire. A correlational analysis was performed to discover if there was a relationship between students’ extrinsic and intrinsic motivation towards their English performance. The results reveal that the intrinsic motivation was strongly correlated with the students’ English performance with r=0.216, p0.05, while the extrinsic motivation showed zero association with the students’ English performance with r=0.125, p0.05. A multiple linear regression analysis was also conducted to investigate the extent that students’ intrinsic and extrinsic motivation predicted their English performance. However, the findings showed that the prediction was only 4.7%. To understand more about the explanation of the findings, a total of 12 students were then interviewed voluntarily. The interview results reveal three themes revolving around the students’ cognitive, affective and social domains in their learning environment. The findings from this study would inform stakeholders to improve the existing teaching and learning models in improving students’ motivation towards English language learning, specifically in the China context.